Evaluation of the Impact of Hadith on Social Change in Various Eras of Islamic History - Hidayatulah Abdul Rachman; Engkos Kosasih; Muhammad Al Mighwar; Mekki Klaina; Md. Thowhidul Islam (Cakrawala: Journal of Religious Studies and Global Society, 2025)
This study analyzes the role of the hadith of the Prophet Muhammad (PBUH) in encouraging social change during three important phases in Islamic history, namely the Khulafaur Rashid, the Umayyad and Abbasid periods, and assesses its relevance in contemporary contexts. This study uses a qualitative approach with a content analysis method on primary and secondary sources that contain hadith and historical records related to social transformation in each period. The results of the study show that during the time of Khulafaur Rashidin, hadith became a normative foundation in organizing socio-political life, including in the distribution of zakat, the protection of minorities, and deliberation in decision-making. In the Umayyad and Abbasid periods, hadith was used as a tool of legitimacy of power, but it also underwent significant codification and standardization, making it an instrument of institutionalized social reform. Contemporary discussions reveal that the values in the hadith remain relevant in promoting social justice agendas, inclusive education, gender equality, and peace. However, challenges arise when the hadith is interpreted textualistically without considering the context and purpose of the shari'a (maqāṣid al-sharī'ah). This study concludes that hadith has great transformative potential if interpreted contextually and progressively, but risks becoming a tool of conservatism if used narrowly. Therefore, hermeneutic and maqāṣid approaches need to be integrated in the understanding of hadith in the modern era.